The Effect of Botox on Women of Productive Age at Evoluskin Batam Clinic - Adrian Saleh Mangkuanom; Gusbakti Rusip; Maya Sari Mutia; Ananda Rahmat Putra; Adrian Nurrachman Tambunan (Fakultas Kesehatan Masyarakat, Universitas Pancasakti, Makassar, 2025)
Botox (botulinum toxin) is a commonly used aesthetic procedure to reduce facial wrinkles, especially in women of reproductive age. Although its physical benefits have been widely recognized, the effect of Botox on the psychological aspects and quality of life of patients still needs to be studied further. This study aims to analyze the impact of Botox use on the patient's skin condition, self-esteem, self-confidence, and quality of life psychologically, socially, and physically. This quantitative study involved 30 respondents selected by purposive sampling. Data were collected through a questionnaire measuring the frequency of Botox use, dosage, and using the Rosenberg Self-Esteem Scale and WHOQOL-BREF to measure quality of life. Data were analyzed using paired t-test and Pearson correlation at 0.05 level of significance. The results showed a significant reduction in wrinkles and skin problems after Botox treatment (mean from 49% to 34%, p=0.003). There was a significant positive relationship between Botox use and self-esteem (r=0.45, p=0.012), self-confidence (r=0.38, p=0.025), and quality of life (r=0.62, p<0.001). These findings indicate that Botox has a positive effect not only on physical appearance, but also on the psychological aspects and overall quality of life of patients.